57 NRF2 REGULATES HYPEROXIA-MEDIATED NOX4 EXPRESSION AND REACTIVE OXYGEN SPECIES PRODUCTION. (1st March 2007) - Pendyala, S.; Gorshkova, I. A.; He, D.; Cho, H.; Kleeberger, S. R.; Natarajan, V.
Abstract : Rationale: We have demonstrated earlier that Nox4, a homologue of Nox2 (gp91phox), is highly expressed in human pulmonary artery endothelial cells (HPAECs) and involved in hyperoxia-induced reactive oxygen species (ROS) production and signal transduction. Nrf2 is a transcriptional factor that is activated in hyperoxia and is known to regulate a number of genes involved in antioxidant defense mechanisms in the lung. Here we have investigated the role of Nrf2 in regulating hyperoxia-induced Nox4 expression and ROS generation in HPAECs. Methods/Results: In HPAECs, mRNA expression of Nox4 is several-folds higher compared with Nox2 (gp91phox), and exposure of cells to hyperoxia (95% O2) resulted in up-regulation of expression of Nox4 and p22phox but not Nox1 or Nox3. Nrf2 is up-regulated in short-term (3 hours) hyperoxia as much as twofold. Down-regulation of Nrf2 mRNA with siRNA attenuated Nox4 expression in normoxic HPAECs; however, enhanced ROS generation under both normoxia and hyperoxia (3 hours). Exposure of Nrf2 wild-type mice to hyperoxia (100% O2 ) for 24 and 48 hours resulted in enhanced Nox4 expression in the lung compared with normoxia. Further, Nrf2 −/− mice exposed to hyperoxia (24 and 48 hours) showed decreased Nox4 expression in the lung compared with normoxia. However, the expression of Nox2 was increased in Nrf2 −/− mice exposed to hyperoxia. Conclusion: These results demonstrate that hyperoxia-induced Nox4 expression and ROS production is regulated by Nrf2 in lung endothelium.